NONAQUEOUS LITHIUM STORAGE ELEMENT - YAMASAKI TAKASHI; KAMIJO TAKESHI; OKADA NOBUHIRO; MORI SHIRO; KANEKO AKIKO (2015)
Provided is a nonaqueous lithium storage element which is obtained by housing an electrode body and a nonaqueous electrolyte solution containing a lithium salt in an outer case, said electrode body being composed of a negative electrode that is composed of a negative electrode collector and a negative electrode active material layer laminated on one or both surfaces of the negative electrode collector, a positive electrode that is composed of a positive electrode collector and a positive electrode active material layer laminated on one or both surfaces of the positive electrode collector, and a separator. This nonaqueous lithium storage element is characterized in that the features (1) and (2) described below are satisfied at the same time with respect to the initial lithium charge/discharge characteristics of a negative electrode active material that is contained in the negative electrode active material layer. (1) The amount of charge is from 1100 mAh/g to 2000 mAh/g (inclusive). (2) The amount of discharge is 100 mAh/g or more at the negative electrode potential of 0-0.5 V.